Are some individuals generally more behaviorally plastic than others? An experiment with sailfin mollies - Gibelli,Julie; Aubin-Horth,Nadia; Dubois,Frédérique (PeerJ, 2018)
Individuals within the same population generally differ among each other not only in their behavioral traits but also in their level of behavioral plasticity (i.e., in their propensity to modify their behavior in response to changing conditions). If the proximate factors underlying individual differences in behavioral plasticity were the same for any measure of plasticity, as commonly assumed, one would expect plasticity to be repeatable across behaviors and contexts. However, this assumption remains largely untested. Here, we conducted an experiment with sailfin mollies (Poecilia latipinna) whose behavioral plasticity was estimated both as the change in their personality traits or mating behavior across a social gradient and using their performance on a reversal-learning task. We found that the correlations between pairwise measures of plasticity were weak and non-significant, thus indicating that the most plastic individuals were not the same in all the tests. This finding might arise because either individuals adjust the magnitude of their behavioral responses depending on the benefits of plasticity, and/or individuals expressing high behavioral plasticity in one context are limited by neural and/or physiological constraints in the amount of plasticity they can express in other contexts. Because the repeatability of behavioral plasticity may have important evolutionary consequences, additional studies are needed to assess the importance of trade-offs between conflicting selection pressures on the maintenance of intra-individual variation in behavioral plasticity.
Keywords: Behavioral plasticity; General plasticity; Individual differences; Sailfin mollies